Design of Information Systems: Things versus People - Bødker, Susanne; Greenbaum, Joan (DAIMI Report Series, 1992)
Information Technology is usually designed using traditional system development techniques and emphaizing conventional management objectives that focus on the information rather than the people in a workplace. This chaper uses research from a gender perspective that highlights the ways that office systems can be designed with peopel in mind. It then applies the gender perspective to explain why Cooperative or Participatory Design can be used to enable system developers and office workers to work together to design applications that better support working practices.